The Vital Role Of Respiratory Therapy In Healthcare. An Update (Journal of Namibian Studies : History Politics Culture, 2023)
Respiratory therapy is a vital component of modern healthcare, encompassing a range of interventions aimed at improving respiratory function and quality of life for individuals with breathing disorders. Respiratory therapists play a pivotal role in assessing, diagnosing, and treating patients, employing a diverse skill set to optimize lung health and alleviate respiratory symptoms. This abstract provides an overview of the key roles and responsibilities of respiratory therapists, highlighting their contributions to patient care, disease management, and emergency response.